2016
DOI: 10.1002/mus.24905
|View full text |Cite
|
Sign up to set email alerts
|

Difference in fascicle behaviors between superficial and deep quadriceps muscles during isometric contractions

Abstract: Muscle-dependent fascicle behaviors were observed during contraction. These findings may provide a mechanistic underpinning for differences in sarcomere length changes, relative force contribution, and blood flow during contraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 17 publications
3
31
0
Order By: Relevance
“…Moreover, during submaximal contraction, 50% of total knee extension movement is explained by vastus intermedius activity 37 . It has also been reported that vastus intermedius fascicles change independently of the knee joint angle, which could influence force production at different joint angles 38 . These characteristics would help explain the close relationships observed between functionality, thickness, and vastus intermedius echo intensity in this study.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Moreover, during submaximal contraction, 50% of total knee extension movement is explained by vastus intermedius activity 37 . It has also been reported that vastus intermedius fascicles change independently of the knee joint angle, which could influence force production at different joint angles 38 . These characteristics would help explain the close relationships observed between functionality, thickness, and vastus intermedius echo intensity in this study.…”
Section: Discussionsupporting
confidence: 64%
“…37 It has also been reported that vastus intermedius fascicles change independently of the knee joint angle, which could influence force production at different joint angles. 38 These characteristics would help explain the close relationships observed between functionality, thickness, and vastus intermedius echo intensity in this study. Incorporating a regression model based on vastus intermedius echo intensity, rectus femoris echo intensity, and vastus intermedius thickness explained 70% of the variance of the 6MWT (P < .001).…”
Section: Discussionmentioning
confidence: 65%
“…This implies that a muscle with a smaller pennation angle change has a smaller blood volume change during muscle contraction. We recently used B‐mode ultrasonography to show that no significant change is present in the pennation angle in the VI during knee extension at 50% MVC compared to rest (rest, 12·7°; 50% MVC, 12·9°, increase of 2%, n = 14), but we did observe a significant increase in the pennation angle in the VL (rest, 14·8°; 50% MVC, 18·4°, increase of 24%, n = 14) (Ando et al ., ). Furthermore, Kawakami et al ., () suggested that a larger pennation angle would result in a greater force component perpendicular to the aponeuroses, which would increase intramuscular pressure.…”
Section: Discussionmentioning
confidence: 97%
“…Second, the effect of pennation changes associated with knee joint rotation on interpretation of EMG data may not be negligible (Mesin et al, 2011). We recently demonstrated VL and VI pennation at knee joint angles of 60°and 110°during sustained isometric contraction at 50% of maximum voluntary contraction using ultrasonography (Ando et al, 2016). The difference in pennation between the two knee joint angles was 5Á6°(60°/110°= 18Á4°/12Á8°) in VL and 2Á8°(60°/110°= 12Á9°/10Á1°) in VI.…”
Section: Discussionmentioning
confidence: 99%